Current medical diagnosis & treatment study guide - edited by Gene R. Quinn (McGraw-Hill, 2013)
Derived from CURRENT Medical Diagnosis & Treatment, the world's most popular annual medical book, this unique study guide delivers case analysis of 80 of the most common topics in internal medicine. It provides a comprehensive and well organized synopsis of each topic, making it an essential study partner for a variety of examinations, including the USMLE Step 2, medicine clerkship shelf exams, ABIM internal medicine boards and recertification exams, adult and family nurse practitioner certification examination, and physician assistant national certifying exam. For practitioners, this quick reference covers patient care for 80 of the clinical problems they are most likely to encounter in daily practice